Approach to the registry standardization of Social Work intervention in adult mental health centers in Catalonia - Martinez Plaza, Esther; Cazorla Palomo, Josep (Cuadernos de Trabajo Social, 2023)
This paper tries to find evidence in the need for a standardization social work intervention in mental health in the form of a unified register. Given the lack of existing elements with which to measure the impact on the discipline’s intervention and the social assessment’s implementation in the sanitary field make the limitations of the Electronic Health History evident, as these are unseen. Therefore, this research focuses on highlighting the deficit of registration tools on the most significant methodological aspects of the discipline, adjusted to the mental health specialisation. According to the catalan model, identifying the theoretical models and its application on professional practice. A methodology qualitative and quantitative is used, which includes the participating observation, a documentary analysis and the administration of a questionnaire addressed to social health workers. The research provides the key aspects and priority dimensions for the social work professionals and allows organizing the information to be recorded. The results support the relevance of developing a structured, operational, and viable tool, that helps categorize the intervention record, with the aim to incorporate it into the information system and to allow the assessment of its applicability and effectiveness.